Pelatihan Pengendalian Nyamuk Vektor Demam Berdarah dengan Lethal MosquiTrap Modification (LMM) di Kecamatan Ampenan, Kota Mataram - Munawir Sazali; Husnul Budiatman Dani; Muhsinul Ihsan; M. Harja Efendi (Prodi Tadris IPA Biologi UIN Mataram, 2024)
The community service was carried out in Ampenan District, Mataram City, West Nusa Tenggara. Larval Monitoring Cadres (Jumantik) as targets or partners for this service activity. The problem faced by partners is the large number of cases of Dengue Hemorrhagic Fever (DBD) in several areas of Ampenan. The solution to conducting outreach and training on the manufacture and use of Lethal MosquiTrap Modification (LMM). Through this activity, it hoped that provide information and skills to target cadres so that they are able to independently make ovitraps as an effort to control the dengue virus vector. The final result of this service is that it is hoped that the community can avoid the dangers of dengue fever. Training activities are carried out in 2 stages, the evaluation is carried out in a separate phase. First, carry out socialization on mosquito traps which was attended by the local RT Head, posyandu cadres and community leaders. Second, training in making mosquito traps called Lethal MosquiTrap Modification (LMM). In this activity, training was provided on making simple mosquito traps and how to apply these traps by the community. The final phase carried out an evaluation process to see the seriousness of residents in using these traps to control the dengue virus vector, namely the Aedes aegypti mosquito.